2003
DOI: 10.1523/jneurosci.23-22-08060.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Cellular Basis for Acetylcholine Inhibition ofCaenorhabditis elegansEgg-Laying Behavior

Abstract: Egg-laying behavior in Caenorhabditis elegans is activated by signaling through the G-protein G(rho)q and inhibited by signaling through a second G-protein, G(rho)o. Activation of egg laying depends on the serotonergic hermaphrodite-specific neurons (HSNs), but the neurotransmitter(s) and cell(s) that signal to inhibit egg laying are not known. Mutants for G-protein signaling genes have well characterized defects in egg laying. Here we present an analysis of mutants for other genes reported to lack inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
175
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(184 citation statements)
references
References 46 publications
8
175
0
1
Order By: Relevance
“…The suppression is dominant ( Figure 1A), and transgenic expression of SUP-1(G84E) restores locomotion and swimming behavior in unc-17(e245) mutant animals. We note that additional unc-17 mutant phenotypes have been reported, including reduced growth rate, small adult size, decreased pharyngeal pumping, reduced defecation rate, and constitutive egg laying Avery 1993;Nguyen et al 1995;Bany et al 2003), and these phenotypes are also suppressed by sup-1 mutations (not shown).…”
Section: Sup-1 Mutantsmentioning
confidence: 54%
See 1 more Smart Citation
“…The suppression is dominant ( Figure 1A), and transgenic expression of SUP-1(G84E) restores locomotion and swimming behavior in unc-17(e245) mutant animals. We note that additional unc-17 mutant phenotypes have been reported, including reduced growth rate, small adult size, decreased pharyngeal pumping, reduced defecation rate, and constitutive egg laying Avery 1993;Nguyen et al 1995;Bany et al 2003), and these phenotypes are also suppressed by sup-1 mutations (not shown).…”
Section: Sup-1 Mutantsmentioning
confidence: 54%
“…The suppression is dominant ( Figure 1A), and transgenic expression of SUP-1(G84E) restores locomotion and swimming behavior in unc-17(e245) mutant animals. We note that additional unc-17 mutant phenotypes have been reported, including reduced growth rate, small adult size, decreased pharyngeal pumping, reduced defecation rate, and constitutive egg laying Avery 1993;Nguyen et al 1995;Bany et al 2003), and these phenotypes are also suppressed by sup-1 mutations (not shown).The SUP-1 protein SUP-1 is a member of the DUF2650 subfamily of STMC6 (single-transmembrane proteins with conserved 6 cysteines) family of proteins; STMC6 proteins are single-transmembrane proteins that have a conserved pattern of cysteines in their N-terminal domains (Pei and Grishin 2012). In addition, many members of the family have cysteine residues predicted to be palmitoylated near the cytoplasmic face of the transmembrane segment.…”
mentioning
confidence: 70%
“…Six hermaphrodite-specific VC neurons, which extend synapses onto egg-laying muscles and neurons, were labeled by the pes-10::GFP reporter, named vsIs13 (Figure 4c). 23 In all, 4% and 6% of young-adult vsIs13 and tm3335;vsIs13 worms lost at least one VC neuron, respectively (Figure 4c). However, at the age of 17 days, 51.7% of vsIs13 worms lost at least 1 VC neurons and 84% of tm3335;vsIs13 worms lost at least 1 VC neuron (Figure 4d).…”
Section: Resultsmentioning
confidence: 87%
“…Acetylcholine can either stimulate egg laying, as demonstrated by the addition of the nicotinic agonist levamisole or inhibit egg laying, by the activation of Ga i/o -coupled muscarinic receptors (GAR-2?) on the HSNs that inhibit neurotransmitter release (Weinshenker et al 1995;Bany et al 2003). Physiologically, the overall effects of acetylcholine appear to be inhibitory (Bany et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…5-HT switches the muscle from an inactive to an active state capable of contraction 1 (Waggoner et al 1998). In contrast, the HSNs, which synapse onto the vulval muscle, appear to express Ga i/ocoupled receptors that inhibit neurotransmitter release and egg laying (Bany et al 2003;Shyn et al 2003).…”
Section: S Erotonin (5-ht) Regulates Key Processes In Nem-mentioning
confidence: 99%